Pengaruh Digitalisasi Produk Perbankan Dan Kualitas Layanan Terhadap Kepuasan Nasabah Pada Bank 9 Jambi - Ayu Feranika; Maria Rosario Borroek; Gunardi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The use of technology today is an effort by banks to compete amid competitors in similar service fields. This study aims to prove empirically whether there is a relationship between digitalization of banking products and digital service quality on customer satisfaction at Bank 9 Jambi. The research method used is using multiple regression analysis with the help of the SPSS 26.0 for windows program. The sampling technique in this study was to use purposive sampling method, so that a sample of 114 respondents was obtained who were customers of Bank 9 Jambi. The results of this study indicate that the banking digitalization variable has an effect on customer satisfaction with a significant value of 0.042 <0.05. The efficieny variable shows significant results with a value of 0.012 <0.05 on customer satisfaction. The fulfillment variable has a significant effect on customer satisfaction with a significant value of 0.002 <0.05. The system availability variable has a significant effect on customer satisfaction with a significant value of 0.006 <0.05. The privacy variable has a significant effect on customer satisfaction with a significant value of 0.001 <0.05. Responsivenes variable has a significant effect on customer satisfaction with a significant value of 0.000 <0.05. The Compensation variable shows results that have no significant effect with a value of 0.185> 0.05. Contact variable shows the results affect customer satisfaction with a value of 0.000 <0.05. Meanwhile, the f statistical test resulted in the simultaneous influence of the independent variables on the dependent variable with a sig level value < α (0.000a < 0.005).